1986
DOI: 10.4141/cjas86-047
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis and Fermentation of Grain-Corn Ensiled at Several Moisture Levels and Under Several Simulated Storage Methods

Abstract: and fermentation of grain-corn ensiled at several moisture levels and under several simulated storage methods. Can. J. Anim. Sci. 66: 451461 . Proteolysis of ensiled grain corn (Zea mays L.) was studied in both whole-kernel and ground forms at initial grain moisture levels ranging from 22 to 36Vo. Three trials simulated and examined the effects of anaerobic fermentation, aerobic preensiling and aerobic postensiling environments on soluble nitrogen (SN) formation (Trials I , 2 and 3, respectively). Sealed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 22 publications
(6 reference statements)
3
36
0
9
Order By: Relevance
“…A higher concentration of lactic acid was found in silages at an earlier maturity stage. It has been demonstrated that a lower percentage of DM, low pH and a higher concentration of WSC in immature crops increase the production of organic acids in produced silage (Goodrich et al 1975;Baron et al 1986;Bal et al 1997). Lactic and acetic acid concentrations were higher in inoculated silages than in the respective control silage.…”
Section: Discussionmentioning
confidence: 99%
“…A higher concentration of lactic acid was found in silages at an earlier maturity stage. It has been demonstrated that a lower percentage of DM, low pH and a higher concentration of WSC in immature crops increase the production of organic acids in produced silage (Goodrich et al 1975;Baron et al 1986;Bal et al 1997). Lactic and acetic acid concentrations were higher in inoculated silages than in the respective control silage.…”
Section: Discussionmentioning
confidence: 99%
“…Esse valor indica que o a condição da pastagem não oferecia oferta adequada de folhas. Oferta de forragem 2 a 3 vezes superiores ao consumo são sugeridos para maximizar o desempenho animal (HODGSON, 1990;BARGO et al, 2003 (PEREIRA et. al.…”
Section: Resultsunclassified
“…Também ocorre aumento da área superficial dos grãos sujeita ao ataque microbiano e principalmente, ocorre o rompimento da densa matriz proteica que envolve os grânulos de amido do grão, resultando em maior digestão do amido no trato digestivo dos bovinos (THEURER et al 1999;SODERLUND, 2006 (BARON et al, 1986;ARRIGONI et. al..,1998), que consequentemente, pode promover a elevação no ganho de peso e/ou na eficiência alimentar dos animais (GOODRICH et al, 1975;HENRIQUE et al, 2007;BASALAN, 2013 (THEURER et al, 1999;LOZANO et al, 2000).…”
Section: Revisão Bibliográficaunclassified
“…Adicionalmente, a proteólise é também um mecanismo intrínseco da fermentação, o que resulta em degradação de proteínas do endosperma (BARON et al, 1986 para milho duro e milho dentado respectivamente. Esta redução é independente do genótipo e é ligada, em grande parte, à diminuição da proporção de amido rapidamente degradável (PHILIPPEAU et al, 1996).…”
Section: Discussionunclassified
“…Enzimas bacterianas são apontadas como responsáveis pela proteólise da matriz proteica que envolve os grânulos de amido (BARON et al, 1986).…”
Section: Amidounclassified